Neuroimaging And Neuropsychological Studies in The Clinic Of Mild To Moderate Brain Injury - Kasimov A.A.; Mamurova M.M.; Qilichov J.G; Narzullayev M.A. (Genius Journals, 2023)
Mild to moderate traumatic brain injury (CBI) dominates the overall neurotrauma structure (80-90%). Despite a relatively good prognosis for mental recovery, in these cases, about 10-15% (according to some data, up to 30%) of patients with mild and about 50% of patients with moderate degrees of CHT develop chronic (persisting for several years after the injury) cognitive deficits.
Keywords: neuropsychology; cognitive function; brain injury